Immunosuppressive and angiogenic cytokine profile associated with Bartonella bacilliformis infection in post-outbreak and endemic areas of Carrion's disease in Peru - Pons M.J. (2017)
Analysis of immune responses in Bartonella bacilliformis carriers are needed to understand acquisition of immunity to Carrion’s disease and may allow identifying biomarkers associated with bacterial infection and disease phases. Serum samples from 144 healthy subjects from 5 villages in the North of Peru collected in 2014 were analyzed. Four villages had a Carrion’s disease outbreak in 2013, and the other is a traditionally endemic area. Thirty cytokines, chemokines and growth factors were determined in sera by fluorescent bead-based quantitative suspension array technology, and analyzed in relation to available data on bacteremia quantified by RT-PCR, and IgM and IgG levels measured by ELISA against B. bacilliformis lysates. The presence of bacteremia was associated with low concentrations of HGF (p = 0.005), IL-15 (p = 0.002), IL-6 (p = 0.05), IP-10 (p = 0.008), MIG (p = 0.03) and MIP-1α (p = 0.03). In multi-marker analysis, the same and further TH1-related and pro-inflammatory biomarkers were inversely associated with infection, whereas angiogenic chemokines and IL-10 were positively associated. Only EGF and eotaxin showed a moderate positive correlation with bacteremia. IgM seropositivity, which reflects a recent acute infection, was associated with lower levels of eotaxin (p = 0.05), IL-6 (p = 0.001), and VEGF (p = 0.03). Only GM-CSF and IL-10 concentrations were positively associated with higher levels of IgM (p = 0.01 and p = 0.007). Additionally, IgG seropositivity and levels were associated with high levels of angiogenic markers VEGF (p = 0.047) and eotaxin (p = 0.006), respectively. Our findings suggest that B. bacilliformis infection causes immunosuppression, led in part by overproduction of IL-10. This immunosuppression probably contributes to the chronicity of asymptomatic infections favoring B. bacilliformis persistence in the host, allowing the subsequent transmission to the vector. In addition, angiogenic markers associated with bacteremia and IgG levels may be related to the induction of endothelial cell proliferation in cutaneous lesions during chronic infections, being possible candidate biomarkers of asymptomatic infections.